THE EFFECT OF COMPETITIVE TRAINING ON TRANSITIONAL SPEED AND HANDLING ACCURACY IN HANDBALL FOR STUDENTS - Shehaib, Hadeel Taleb Mohammed; Sarhan, Qusay Ahmed; Farhan, Alia Hussein; Tahseen, Tahseen Hosni (Journal Olahraga Rekat (Rekreasi Masyarakat), 2026)
Background. Through the researcher's observation and follow-up of the practical lectures for the handball course, she noticed a decrease in the amount of physical and skill performance among fourth-year students in the Department of Physical Education - Dijlah Private College, especially in transitional speed and passing accuracy. The researcher attributes the reason for this decrease to the teacher's neglect of competitive training and the focus on using regular training, which led to the students feeling bored, distressed, and lacking motivation and desire to accomplish the tasks assigned to them during the educational units. Objectives. The research aimed to develop competitive training programs for students' transitional speed and handling accuracy in handball, as well as to identify the impact of these competitive training programs on students' transitional speed and handling accuracy. Method. The researcher followed an experimental approach using a pre-/post-test design with two equivalent groups, The sample consisted of (30) students representing fourth-year students in the Department of Physical Education and Sports Sciences at Dijlah Private College for the academic year (2025-2026). The researcher conducted the homogenization process for the research sample and performed the equivalence process for the two groups in the dependent variables (transitional speed and accuracy of handling from head level) based on the pre-measurements, The competitive training was then applied to the experimental group for (4) weeks at a rate of (2) units per week. After that, post-tests were conducted, in which the researcher ensured that they were conducted under the same conditions and circumstances as the pre-tests. Results. The results were then analyzed using appropriate statistical methods, and based on these results; the researcher concluded that competitive training plays a significant role in improving students' transitional speed and overhead ball handling accuracy with handball. Furthermore, the experimental group demonstrated a clear and substantial superiority in post-test measurements over the control group in both transitional speed and overhead ball handling accuracy with handball. Conclusion. Competitive training plays a major role in improving transition speed and accuracy of overhead handling with handball for the students. The experimental group showed a significant and clear superiority in the dimensional measurements over the control group in the transitional speed and accuracy of handling from head level with the handball. The control group showed a remarkable superiority in the post-test measurements over the pre-test measurements in transitional speed and accuracy of handling from head level with the handball.